Aplikasi Remote Sensing dan Sig Untuk Pemetaan dan Informasi Sumberdaya Lahan Subak Sawah di Kecamatan Kuta dan Kuta Utara, Kabupaten Badung - DEWA GEDE SUARJAYA; INDAYATI LANYA; I GUSTI PUTU RATNA ADI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
Application of Remote Sensing and GIS for Mapping and Information Resources in Wetland of Subak in Kuta and North Kuta, Badung Regency Subak in this research is a wetland that has spatial data. Wetland subak during this uncharted spasial basis and yet the existence of the information resources of subak. Subak database based information dan communication technologi (ICT) is indispensable in agricultural development in general. This research was done in Kuta and North Kuta, Badung, Bali from September 2016 to March 2017. The research method includes : (1) library studies, (2) analysis of satellite imagery conducted using Quickbird 2012 and Quickbird 2017, (3) surveys, and (4) arrangement of database resource.The result of digitized satellite images in 2017 retrieved 21 subak area of 1007.39 ha in Kuta and North Kuta. BPS data (Statistics Indonesia, 2016) retrieved 22 subak area of 1316 ha. Subak Ulun Tanjung located in the Legian Village has not paddy fields since 2006. Land resources information system of subak is very accessible and fast through the technology of Geografis Information Systems (GIS).